ASYNCHRONOUS ORTHOGONAL DEMODULATOR - MISAIZU KIMIHIDE; ONISHI HIROSHI (1991)
PURPOSE:To realize an asynchronous orthogonal demodulator operated stably even in a transmission line where transmission line distortion due to multi-path exists without use of a reference carrier recovery circuit. CONSTITUTION:A frame format of a transmission signal consists of a 1st frequency correction symbol 1, several tens to several hundreds symbols of random series and a 2nd frequency correction symbol 2 and a data. A reception signal subjected to transmission distortion due to multi-path is detected by an asynchronous orthogonal demodulator. A frequency compensation device estimate a local oscillating frequency of the asynchronous orthogonal demodulator and a frequency offset of a reception carrier from the 1st and 2nd frequency correction symbols to compensate the phase of the detected output. A base band complex number equalizer eliminate the transmission line distortion from the detection output subject to phase correction. Through the constitution above, the demodulator is operated stably even in a transmission line having transmission line distortion due to multi-path, no reference carrier recovery circuit is required and the constitution is simplified.